A comparison of two backstroke starts - Theut, K. M.; Jensen, R. L. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
This study investigated the effect of a staggered or parallel foot placement on horizontal distance and velocity at which the swimmer moved away from the block to the point that the hands entered the water during a backstroke start. Ten NCAA division II collegiate women swimmers were filmed from above water performing three of each of the two types of starts. An underwater camera was used to capture stability aspects of the feet prior to and during the start. There was no significant difference (p > 0.05) seen in average velocity or horizontal distance that the swimmer traveled when comparing both types of starts. The Chi squared analysis found no significant differences in movement of the feet during the two backstroke starts (p > 0.05). Further research should be performed with increased practice time of both starts and to compare differences between genders.